KERAGAMAN KEYAKINAN SEBUAH TANTANGAN DAN HARAPAN BAGI KERUKUNAN BERAGAMA (STUDI PEMIKIRAN TH SUMARTANA TENTANG KERAGAMAN KEYAKINAN) - Nugroho Nugroho (JIA (Jurnal Ilmu Agama), 2016)
Intensive conflicts occur when it enters an era of globalization. Sumartana, the Catholic pastor of Jogjakarta, giving the idea that it needs for a new approach of looking at religion in order to prevent the religious conflict. According to Sumartana , all Humans have "nur ilahi”  the divine light. All human being in the world is created by God. Man is not the demonic creature. Basically, humans are "good", because it has the "divine light". In Christian theology man is referred to "the map  or  the  image  of  God".  Sumartana  also  suggested  that  the  dialogue  is  not  scheduled "competition of truth". Dialogue does not choose the champions of religion. Dialogue is not a fight for  the  number  one.  Religion  according  Sumartana  should  have  a  commitment  to  humanity.  The mission of religion is humanistic, not just converting people to Christianity.  So missiology is not heresiologi which is an attempt to condemn other people. Instead the mission is to improve the lives of  people  and  society  as  a  whole.  Sumartana  proposes  a  liberative  Christology  that  combines "liberation theology" and "theological dialogue" with the starting point at the "historical Jesus and